The Prehistory of the Crusades: Toward a Developmental Taxonomy - Reynolds, Burnam W. (History compass, 2008)
The Crusades are frequently depicted as if they materialized without sufficient antecedence in the late eleventh century. On those occasions when the lines of development that produced this epochal movement are discussed, they are often examined in a piece-meal and non-chronological fashion. The end result is to downplay the important conceptual preconditions necessary for a Crusade and to convey the impression that the endeavor either sprang ‘full blown’ from nowhere or was created on the fly. This article suggests that the components of crusading must be identified and ordered into a type of chronological taxonomy so that the full import of the movement might be understood. While there are numerous, and excellent, histories of the Crusades, I suggest a workable prehistory of this trans-epochal phenomenon is not only desirable, but essential. Borrowing from the well-established field of prehistory, I seek to place the antecedents for crusading into paleo-, meso-, and neo-prehistory categories. In this way the sequential emergence of the preconditions of crusading may better illuminate its eventual emergence.